2017
DOI: 10.1136/jmedgenet-2017-104586
|View full text |Cite
|
Sign up to set email alerts
|

Hypothesis: lobe A (COG1–4)-CDG causes a more severe phenotype than lobe B (COG5–8)-CDG

Abstract: The conserved oligomeric Golgi (COG) complex consists of eight subunits organized in two lobes: lobe A (COG1-4) and lobe B (COG5-8). The different functional roles of COG lobe A and lobe B might result in distinct clinical phenotypes in patients with COG-CDG (congenital disorders of glycosylation). This hypothesis is supported by three observations. First, knock-down of COG lobe A components affects Golgi morphology more severely than knock-down of COG lobe B components. Second, nearly all of the 27 patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 44 publications
(19 reference statements)
1
18
0
Order By: Relevance
“…Comparisons between the clinical phenotype of COG-CDGs should take into consideration the effect of the mutation on the affected COG subunit. In the recent retrospective analysis of COG-CDGs, Haijes et al [ 118 ] made such a comparison and concluded that lobe A mutations are more detrimental than lobe B mutation, but the discussion is not settled mainly because of the small number of known mutations and lack of robust data on these patients.…”
Section: Discussionmentioning
confidence: 99%
“…Comparisons between the clinical phenotype of COG-CDGs should take into consideration the effect of the mutation on the affected COG subunit. In the recent retrospective analysis of COG-CDGs, Haijes et al [ 118 ] made such a comparison and concluded that lobe A mutations are more detrimental than lobe B mutation, but the discussion is not settled mainly because of the small number of known mutations and lack of robust data on these patients.…”
Section: Discussionmentioning
confidence: 99%
“…To correlate phenotypic severity to the predicted consequences of the POLR2A variant and to find an explanation for the wide phenotypic spectrum, an ad hoc severity score was conceived. 44 It was calculated as follows: each tabulated item that was present (þ) in the individual scored 1 point and each absent item (À) scored 0 points ( Table 1). The items ''sit without support,'' ''walk well,'' and ''brain magnetic resonance imaging (MRI) abnormalities'' were calculated as follows: ''sit without support'' at <12 months scored 0 points, at 13-18 months scored 1 point, at 19-30 months scored 2 points, and at >30 months scored 3 points; ''walk well'' at <24 months scored 0 points, at 25-30 months scored 1 point, at 31-48 months scored 2 points, and at >48 months scored 3 points; no brain abnormalities scored 0 points, wide ventricles and/or delayed myelination scored 1 point, and white matter abnormalities scored 2 points.…”
Section: Assessing Phenotype-genotype Correlationmentioning
confidence: 99%
“…During Golgi trafficking, resident proteins, like glycosylation enzymes, require recycling from the late Golgi to the early Golgi cisternae to maintain the integrity of the nontemplate driven glycosylation system ( Glick et al , 1997 ; Glick and Nakano 2009 ; Mironov et al , 1997 ; Pelham 2001 ). Glycosylation enzymes MAN2A1, MGAT1, B4GALT1, and ST6GAL1 are mislocalized in COG-deficient cells ( Shestakova et al , 2006 ; Pokrovskaya et al , 2011 ), and all COG subunits, with the exception of COG3, have mutations described as contributing to human congenital disorders of glycosylation (CDG) ( Climer et al , 2015 ; Haijes et al , 2018 ).…”
Section: Introductionmentioning
confidence: 99%